Eco-architecture VIII harmonisation between architecture and nature - Hernández, S. (Santiago), 1951-; Chías Navarro, Pilar (WIT transactions on the built environment ;, 2020)
This volume originates from the 8th International Conference on Harmonisation between Architecture and Nature and deals with topics such as building technologies, design by passive systems, design with nature, cultural sensitivity, life cycle assessment, resources and rehabilitation and many others including case studies from around the world.